Marian S. Carson collection of manuscripts (primary record) - Carson, Marian S.; Marian S. Carson Collection (Library of Congress)
Correspondence, family papers, journals, political documents, legal and financial records, military records, broadsides, ephemera, and other papers relating to American military, political, and social history. Documents the founding of the nation, shaping of the national government and judicial system, American endeavors in the arts, commerce, education, finance, industry, law, literature, medicine, religion, science, and technology, and daily life in early America. The focus of the collection is Philadelphia, Pa.
Subjects include African-American history, Native American history, women's history, British colonial history, geographic expansion, role of the Continental Congress, political partisanship, development and expansion of the U.S. Navy, French and Indian War, Revolutionary War, War of 1812, Civil War, founding and early development of Pennsylvania, other state and local history, urban life in America, slavery, labor, communes, transportation, travel, telegraph, banking, currency, postal service, pony express, ships and shipping, booksellers, printers and printing, publishers and publishing, advertising, photography, textile industry, papermaking industry, decorative arts, fine arts, performing arts, domestic arts, food and cooking, wine making, liquor industry, tobacco, sports, holidays, circuses, fairs, expositions, the Centennial Exhibition in Philadelphia in 1876, libel trial of Thomas Cooper, Fairmount Park, public institutions such as hospitals and schools, Quaker schools including a school for African-Americans, and the Free Quaker Meetinghouse in Philadelphia.
Individuals represented include Joel Abbot, Alexander Addison, Robert Aitken, Chester Alan Arthur, John Ashmead, Benjamin Franklin Bache, Josiah Bartlett, Big-Tree, William Bingham, Joseph Bloomfield, William Bradford, James Bringhurst, Joseph Bringhurst, James Buchanan, Edward Burd, Charles Cadwalader, John Cadwalader, Archibald Carey, Mathew Carey, Charles Carroll, Grover Cleveland, Benjamin Hornor Coates, Samuel Coates, William Cobbett, Cornplanter, Caleb Cresson, John Dickinson, James Duane, John Dunlap, Peter Evans, Elizabeth Graeme Ferguson, Andrew H. Foote, Benjamin Franklin, Albert Gallatin, Stephen Girard, Half-Town, Alexander Hamilton, John Hancock, Robert Hare, Rutherford Birchard Hayes, Joseph Henry, J. William Hoffman, Francis Hopkinson, Eliza Hornor, Sarah Hornor, Isaac Howell, Charles Evans Hughes, Joshua Humphreys, Samuel Huntington, John Jay, Thomas Jefferson, Edward Jenner, Rufus King, Henry Lee, Peter Legaux, Abraham Lincoln, James Madison, John Marshall, Luther Martin, Timothy Matlack, John A. McAllister, James McHenry, Thomas Mifflin, James Monroe, Robert Morris, John Nicholson, George Ord, William Paterson, Elizabeth Palmer Peabody, Charles Willson Peale, William Penn, Philip Syng Physick, Timothy Pickering, James K. Polk, Eli K. Price, William Rawle, George Read, Joseph Reed, Robert Riggs, David Rittenhouse, Franklin D. Roosevelt, Theodore Roosevelt, Nellie Lincoln Rossiter, Benjamin Rush, William Rush, Thomas Say, Edward Shippen, William Shippen, Boyd M. Smith, Baron Friedrich Wilhelm Ludolf Gerhard Augustin von Steuben, Robert Stewart, William H. Taft, John Chew Thomas, Charles Thomson, Edward Tilghman, John Todd, Robert Troup, Martin Van Buren, Garret D. Wall, Richard Waln, Bushrod Washington, George Washington, Samuel Wetherill (1736-1816), Samuel Wetherill (1764-1829), William White, James Wilson, Woodrow Wilson, Caspar Wistar, William Wallis Woodward, and Jasper Yeates.
Families represented include the Bennett, Biddle (Bedell), Bloomfield, Booth, Bradford, Carson, Clayton, Coates, Cresson (Creason), Doan, Hornor (Horner), McAllister, Peale, Penn, Rittenhouse, Stacey (Stacy), Waln, Wetherill, and Yarnell families.
Institutions and organizations represented include the American Philosophical Society, Asylum Company, Library Company of Philadelphia, Pennsylvania Horticultural Society, Pennsylvania Hospital, Overseers of the Poor, Society of Free Quakers, State Society of the Cincinnati of Pennsylvania, United Company of Philadelphia for Promoting American Manufactures, and United States Sanitary Commission.
Primary record for Marian S. Carson collection of manuscripts.
Continuation record mm2009085506 consists of the geographic subject headings represented in the collection.
Continuation record mm2009084367 consists of the individuals, families, institutions, and organizations represented in the collection.
Library of Congress Rare Book and Special Collections Division.
Library of Congress Geography and Map Division.
transferred to Library of Congress Music Division.
Keywords: Advertising -- United States; African Americans -- Education; African Americans -- History; American literature; American literature -- Pennsylvania -- Philadelphia; Art -- United States; Arts -- Pennsylvania -- Philadelphia; Arts -- United States; Banks and banking -- United States; Booksellers and bookselling -- United States; Circus -- United States; City and town life -- United States; Communal living -- United States; Cooking -- United States; Courts -- United States; Decorative arts -- United States; Education -- Pennsylvania -- Philadelphia; Education -- United States; Exhibitions -- United States; Fairs -- United States; Finance -- Pennsylvania -- Philadelphia; Finance -- United States; Holidays -- United States; Hospitals -- United States; Indians of North America -- History; Industries -- Pennsylvania -- Philadelphia; Industries -- United States; Judicial power -- United States; Labor -- United States; Law -- Pennsylvania -- Philadelphia; Law -- United States; Liquor industry -- United States; Local history -- United States; Medicine -- Pennsylvania -- Philadelphia; Medicine -- United States; Money -- United States; Paper industry -- United States; Parks -- Pennsylvania -- Philadelphia; Performing arts -- United States; Photography -- United States; Political parties -- United States; Pony express; Postal service -- United States; Printers -- United States; Printing -- United States; Publishers and publishing -- United States; Quaker church buildings -- Pennsylvania -- Philadelphia; Quakers -- Pennsylvania -- Philadelphia; Schools -- Pennsylvania -- Philadelphia; Schools -- United States; Science -- Pennsylvania -- Philadelphia; Science -- United States; Shipping -- United States; Ships -- United States; Slavery -- United States; Social history; Sports -- United States; Technology -- Pennsylvania -- Philadelphia; Technology -- United States; Telegraph -- United States